The Influence of Parenting on Problematic Behavior in Children - Novi Widiastuti; Ihat Hatimah; Elih Sudiapermana; Asep Saepudin (Universitas Negeri Semarang, 2025)
Problem behavior in adolescents (12-17 years) has become a serious concern in the social environment. The parenting style applied by parents can play an important role in shaping this behavior. This study investigates the effect of various parenting styles on problem behavior in adolescent children. The research sample consisted of 100 parents in Bandung with children aged 12-17 with problem behavior. The sample was selected through stratified random sampling techniques to ensure good representation. Data was collected through a questionnaire that measures children's parenting styles and problem behavior. Data analysis involved regression analysis and quantitative correlation. The regression analysis showed that each parenting style contributes differently to problematic behavior. Permissive parenting style showed a significant effect (p < 0.001), followed by authoritarian parenting styles (p < 0.001) and authoritative (p = 0.022). However, uninvolved parenting style had the most significant impact (p < 0.001). Quantitative correlation also indicated a strong relationship between permissive and uninvolved parenting styles and problematic behavior (r = 0.677 and r = 0.994). Parenting styles have different influences on problematic behavior in adolescent children. These findings provide a deeper understanding of how each parenting style plays an important role in forming problem behaviors in children. This study makes a new contribution to understanding the relationship between parenting style and problem behavior in adolescent children by highlighting the role of quantitative and statistical analysis in uncovering this relationship.